Fertile Ground: The Biopolitics of Natalist Populism - Rasmussen, Claire (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2023)
Fears of immigration and demographic change have fueled nativist, pro-natalist movements that support the reproductive, heteronormative family as a vital political project shaping their rhetoric and politics. This paper argues that right-wing populist movements can be situated within heteroactivsm, as reactionary movements positioning themselves against challenges to the heteronormative family. I suggest that understanding the populist character of these movements can help theorize why so many right-wing populists echo specific claims about gender and race. By situating their political claims in biological claims about sex, gender and race, these movements contrast themselves with abstract ideals of universal human rights, neoliberal rationality, and cosmopolitan globalism, embracing the traditional family, gender norms, and heterosexual reproduction. They encourage normative family promoted through state policy of rewarding proper families and punishing improper social reproduction—whether literal reproduction or the cultural reproduction of values. Tracing the broad outlines of a political project anchored in the reproductive bodies of women, I argue for greater attention to the ways the heteroactivist project is central to right-wing populism and its multi-scalar manifestations.